An Analysis of Five Factors of Personality Traits of Turkish Late Adolescents According to Computer Anxiety - Aslan, Sevda (International Journal of Humanities and Social Science Research, 2015)
The aim of this study was to analyze the relationship between five factors of personality traits of Turkish late adolescents and computer anxiety in a Turkish study group. The study group consisted of 119 students: 97 females and 22 males. The study data was collected using the Adjective-Based Personality Test and Personal Information Form. Findings of this study revealed that there is no significant statistical difference among the participant scores for the Personality Test Based on Adjectives (ABPT)’s dimensions of emotional instability/neuroticism, extraversion, openness to experience, agreeableness and responsibility, owning computers and anxiety during the use of computers.